[Rezension von: Karrin Hanshew, Terror and Democracy in West Germany] - Mausbach, Wilfried (The American historical review, 2013)
West Germany's domestic terrorism, and in particular the umbilical cord connecting it to 1960s protests, continue to be major fields of contestation in the country's history. Those expecting Karrin Hanshew to intervene in this politically charged debate or to submit yet another history of the Red Army Faction (RAF) will be disappointed. Instead, she takes a longer-term and much more profound approach.Hanshew is certainly not alone in considering the German Autumn, the culmination of West German terrorism in the fall of 1977, to be a “transformative event” (p. 8). Yet in explaining this assertion she turns our attention to the uneasy relationship between political stability and civil liberties, tracing German attitudes toward that democratic conundrum back to the interwar years. Consequently, “democracy” is the author's initial concern, and the reader will have to get through a third of the book before the analysis arrives in the 1960s and another twenty pages before “terror” takes center stage. Prior to this, Hanshew develops an original framework based on the German constitutional concept of wehrhafte Demokratie (militant democracy), which allows her to evaluate West Germany's struggle with domestic terrorism from a new and innovative vantage point.